2020
DOI: 10.1017/wsc.2020.18
|View full text |Cite
|
Sign up to set email alerts
|

Band sowing with hoeing in organic grains: II. Evidence of improved weed management in spring wheat, oats, field peas, and flax

Abstract: The long-term success of weed management programs requires that all crops in a rotation receive satisfactory weed control. Band sowing with inter-band hoeing has been proposed as an innovative weed management strategy for grain crops. In the band-sowing system, crops are sown in a broadcast pattern within a band of some chosen width (here we selected 12.7 cm); weeds between bands are controlled with inter-band hoeing, with or without so-called “blind cultivation,” for example, tine harrowing. Alteration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Instead of planting in standard rows where the crop is crowded into a narrow line, sowing in a random pattern within a 5-to 20-cm wide band may reduce competition among crop plants while increasing intraband weed suppression. However, outcomes have varied among studies evaluating band sowing and hoeing (McCollough et al 2020a(McCollough et al , 2020bSpeelman 1975), and further research is needed to validate the theoretical benefits of this strategy.…”
Section: Additional Intrarow Weed Management Strategies In the Hoed C...mentioning
confidence: 99%
“…Instead of planting in standard rows where the crop is crowded into a narrow line, sowing in a random pattern within a 5-to 20-cm wide band may reduce competition among crop plants while increasing intraband weed suppression. However, outcomes have varied among studies evaluating band sowing and hoeing (McCollough et al 2020a(McCollough et al , 2020bSpeelman 1975), and further research is needed to validate the theoretical benefits of this strategy.…”
Section: Additional Intrarow Weed Management Strategies In the Hoed C...mentioning
confidence: 99%
“…Furthermore, like annual flax, Lewis flax is likely a weak competitor against weeds, and both seed quality and yield may be reduced because of competition from weeds (Bilalis et al, 2012; Ehrensing, 2008; Flax Council of Canada, 2022; McCollough, Gallandt and Molloy, 2020). A meta-analysis of the organic:conventional yield gap by de Ponti et al (2012) found that average organic flax yields are only 65% of typical conventional yields.…”
Section: Introductionmentioning
confidence: 99%